SUPERPARAMAGNETIC COBALT NANOCOMPOSITES SYNTHESIZED BY SOLVOTHERMAL SYNTHESIS IN A SINGLE STEP - Carolina Alicia Castillo Vicencio; Paula Santana (Journal of the Chilean Chemical Society, 2021)
In this work we are reporting the synthesis and characterization of superparamagnetic cobalt nanocomposites obtained from the direct reduction of cobalt(II) salts on matrices of graphene (G) and carbon nanodisks/nanocones (Ndc) in the presence of L-serine under solvothermal conditions. The synthesized nanocomposites were characterized by X-ray powder diffraction techniques identifying in all cases the peaks associated to the matrix (G or Ndc) and three peaks at 2θ values of 44,2; 51,5; 75,8°, which correspond to the Miller indices (111), (200), (220), characteristic of a face centred cubic Co0 phase. The SEM images of cobalt nanocomposites show that the use of an matrix changes the size and distribution of the metallic agglomerates, being possible to observe a more homogenous dispersion of the cobalt agglomerates on the Ndc matrix surface. Cobalt nanocomposites have a superparamagnetic behaviour presenting Hc values of 14 and 60 Oe for NPs-Co0/G and NPs-Co0/Ndc respectively. The superparamagnetic property of the cobalt nanoparticles and unique properties of the matrix would generate a magnetic material with interesting properties to be studied. More research is needed to give it a potential application.